1984
DOI: 10.1111/j.2044-8325.1984.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Frustration in organizations: Relationships to role stress, climate, and psychological strain

Abstract: A measure of environmental frustration was constructed and administered to 40 1 young graduate engineers working in industry. Self-reported frustration was associated with the dependent variables ofanger reactions, latent hostility, job dissatisfaction and, to a lesser extent, work-related anxiety. Evidence from multiple regression analysis indicated that organizational climate, role stress, and social support all contributed to the level of environmental frustration. These variables were also associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 4 publications
2
68
0
1
Order By: Relevance
“…The negative outcomes of a high workload are well documented and include frustration, stress and counterproductive work behavior, including aggression (Keenan & Newton, 1984;Matthews et al, 2002;Penney & Spector, 2005). We argue that this is yet another impetus for organizations to consider implementing primary preventive, stress management techniques (Quick, Quick, Nelson, & Hurrell, 1997) such as reducing heavy workloads and staffing adequate numbers of individuals to meet organizational demands.…”
Section: Discussionmentioning
confidence: 95%
“…The negative outcomes of a high workload are well documented and include frustration, stress and counterproductive work behavior, including aggression (Keenan & Newton, 1984;Matthews et al, 2002;Penney & Spector, 2005). We argue that this is yet another impetus for organizations to consider implementing primary preventive, stress management techniques (Quick, Quick, Nelson, & Hurrell, 1997) such as reducing heavy workloads and staffing adequate numbers of individuals to meet organizational demands.…”
Section: Discussionmentioning
confidence: 95%
“…With reference to this finding, Gignac and Appelbaum (1997) established that having too many tasks and their linkage to deadlines leads to time pressure. Also, Keenan and Newton (1984) found strong association between anxiety and having too much work to do in the time available. Moreover, complexity at work results in high workload and high role conflict (Tummers et al, 2002).…”
Section: Workload and Job Pressurementioning
confidence: 94%
“…With reference to this, Chang and Lu (2007) emphasised that organisational culture valuing human relations, provide people with social support network and thus, help reduce stress among them. Further, Keenan and Newton (1984) suggested that in order to reduce frustration among the individuals in the organisation, an atmosphere of warmth and support as a whole is more important than the support received from the immediate superior. The variable, viz., lack of mutual trust and unsupportive culture, received the highest factor loading while insincere implementation of dignity-related policies was the lowest contributor for the factor (Table 1).…”
Section: Indifferent Organisational Attitudementioning
confidence: 98%
“…Among students, frustration is the emotional feeling arising from the experience of having one's goals interrupted or blocked and is characterized by unlikely expectations for overcoming obstacles (Price, Barrell and Barrell, 1985;Roseman et al, 1994). In an organization, data indicates that most employee frustration arises from a perception of interference with an individual's ability to carry out his day-to-day duties eectively (Keenan and Newton, 1984). Based on these ®ndings, we propose that the aective response of an employee attributing the source of felt stress to the situation (impersonal and uncontrollable by either the organization or self) is frustration.…”
Section: Speci®c Aective Responses To Causal Dimensionsmentioning
confidence: 97%